2023
DOI: 10.2196/41099
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Traditional Chinese Medicine–Based Mobile Health App for Individuals With Prediabetes: Randomized Controlled Trial

Abstract: Background Traditional Chinese medicine (TCM) theories assert that body constitution and meridian energy lay the foundation for disease prevention. TCM-based health concepts have not yet been incorporated into mobile health (mHealth) apps for individuals with prediabetes. Objective The aim of this study was to examine the effectiveness of a TCM mHealth app for individuals with prediabetes. Methods This rando… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…[7][8][9][10][11][12] Traditional Chinese medicine constitution theory believes that through diet, exercise, 28 drug conditioning and other methods can improve people's unbalanced constitution, so as to prevent the occurrence of disease, or improve the condition of patients who have been sick, and promote the recovery of disease. 29,30 Therefore, the TCM constitution has enormous potential for disease prevention and treatment applications. Our research revealed that among all patients with COVID-19, 43.8% had a balanced constitution, consistent with the constitution proportion in the Chinese population, 31 indicating that all constitutional groups are susceptible to the COVID-19 Omicron variant.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Traditional Chinese medicine constitution theory believes that through diet, exercise, 28 drug conditioning and other methods can improve people's unbalanced constitution, so as to prevent the occurrence of disease, or improve the condition of patients who have been sick, and promote the recovery of disease. 29,30 Therefore, the TCM constitution has enormous potential for disease prevention and treatment applications. Our research revealed that among all patients with COVID-19, 43.8% had a balanced constitution, consistent with the constitution proportion in the Chinese population, 31 indicating that all constitutional groups are susceptible to the COVID-19 Omicron variant.…”
Section: Discussionmentioning
confidence: 99%
“…We read the study by Chung et al [ 1 ], which evaluated the effectiveness of a mobile health (mHealth) app based on traditional Chinese medicine (TCM) in patients with prediabetes. This randomized controlled trial showed that the TCM mHealth app improved physical energy, fitness, and quality of life in patients with prediabetes.…”
mentioning
confidence: 99%
“…Third, an interaction is an action that occurs when 2 or more objects interact with each other [ 4 ]. Since many variables are described in the first table of Chung et al’s [ 1 ] paper, prespecified subgroup analyses based on these variables are necessary. Subgroup analyses based on age, gender, BMI, body composition, and blood pressure were not performed in this study.…”
mentioning
confidence: 99%
“…We appreciate the thoughtful comments by Lin [ 1 ] on our study [ 2 ]. We have mentioned that the limitations of our study include a small sample size and a short follow-up period.…”
mentioning
confidence: 99%